Marriage under the age of legal perspective on Sasak tribe in Indonesia - Ihsan Ihsan (Harmoni Sosial: Jurnal Pendidikan IPS, 2020)
The existing tradition of marriage under age (Merariq Kodeq), this research aims to understand the consciousness of the national law, which prevails in the middle of the community with the existence of the marriage laws related to the age of marriage. This study used a qualitative approach to know the factors causing, the form of offense, impact, and effort of government in marriage underage in the Parampuan village Lombok Barat regency. The study results are as follows. Factors affect the Merariq Kodeq among the others because of the low financial of a family, factors of low public education, personal factors influenced by environment intercommunication, factors parental concern to the intercommunication of his son, cultural factors that still adopted the community. Abuses that are not in accordance with the provisions of the constitution based on Indonesian law system marriage, which the age of children in doing marriage, the validity of marriage did not participate noted in the office of religious affairs—the rights of the child and teenage as the young generation. The impact of that occurs as a result of Merariq Kodeq is premature pregnancy, dropping out of school, domestic violence, divorce, psychological trauma as well as vulnerable to marriage in below the hands. The government commitment to socializing in the village, guidance, the documentary movie about the dangers of marriage on the below age, and the information center for counseling sex education for teenagers.